Legal Protection of UMKM in Indonesia in Relation to the Legality of Securities Crowdfunding - Ayu, Adelia Setya; Muryanto, Yudho Taruno (International Journal of Sustainability in Research, 2024)
Seeing the potential of UMKM to support the national economy, the Indonesian government has begun to shift its focus to empowering UMKM. The problem that is mushrooming in the implementation of UMKM is regarding capital. This was made worse by the COVID-19 outbreak in 2020 which made it difficult for UMKM to obtain capital. Along with the recovery of UMKM in Indonesia after COVID-19, the Indonesian government has issued various stimuli. One of them is by issuing Financial Services Authority Regulation Number 57/POJK.04/2020 of 2020 which essentially regulates Securities Crowdfunding ("SCF"). These arrangements have been updated to accelerate the empowerment of UMKM in Indonesia through Financial Services Authority Regulation Number 16/POJK.04/2021 of 2021. This research uses normative juridical methods and is based on secondary data. This research seeks to analyze how the financing model works and the implementation of regulations for implementing securities crowdfunding in supporting UMKM. The results of this research show that the regulatory role of SCF has supported MSME activities in Indonesia through various conveniences inherent in it.